Membangun Ketahanan Berbasis Komunitas dalam Mengurangi Risiko Bencana di Desa Pilomonu Kabupaten Gorontalo - Syahrizal Koem (Jurnal Pengabdian Pada Masyarakat, 2019)
BUILDING RESILIENCE BASED COMMUNITIES IN DISASTER RISK REDUCTION IN THE PILOMONU VILLAGE GORONTALO REGENCY. This article discusses the concept of community-based disaster risk reduction so that it can realize community resilience to disasters. The implementation of community-based disaster resilience programs uses participatory approaches, observation, interviews, socialization, training, and Forum Group Discussion (FGD). The establishment of the PRB and TSBM forums received a positive response from the community because Pilomonu Village was classified as a disaster-prone village, especially landslides and floods. Analysis of the resilience index conducted by the forum based on indicators and achievements found that Pilomonu Village is included in the category of 'village not yet strong' and the level of preparedness is low. Indicators of community disaster resilience that have been established and adjusted in the document can be the main focus of all parties related to disaster risk management. The PRB and TSBM forum are those who have overall access to improving disaster resilience because forum skills in involving stakeholders are a determinant of the success of disaster resilience to lower-level communities. Integration between the Pilomonu Village government program and disaster risk reduction forums can guarantee the sustainability of forum performance.